Peran Manajemen Pelayanan Publik dalam Mewujudkan Pelayanan yang Efektif dan Efisien - Akbar, Merly Septia Afsani; Tjenreng, Muhammad Baharuddin Zubakhrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Effective and efficient public services have become one of the top priorities in government management in various countries. In this context, this research aims to identify the role of public service management in realizing effective and efficient services by utilizing various secondary sources through literature studies. The effectiveness of public services is measured by the extent to which services can meet public expectations, while efficiency relates to the optimal use of resources in delivering services. A qualitative approach is used in this research with a literature study method that examines various theories, policies, and practices related to public service management. The results showed that good public service management can improve effectiveness by paying attention to the quality of interaction between officers and the public, speed, accuracy, and ease of access to services. The use of information technology such as e-government systems and management information has proven effective in accelerating service flow, increasing transparency and accountability. Meanwhile, efficiency can be achieved by simplifying administrative procedures, reducing bureaucracy, and optimizing the use of trained human resources.